The Roles of Youth in Preserving Local Cultures to Develop Tourism in Sabang City - Lubis, Faris Yusuf; Sibarani, Robert; Lubis, Suwardi (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aimed to analyze youth roles in protecting, developing, and utilizing local cultures to develop tourism in Sabang. This type of research was descriptive research with a qualitative approach; that is, the research is carried out in natural conditions (natural settings). The results showed that youth's role in protecting local Culture to develop tourism in the city of Sabang could be seen with youth's enthusiasm in publishing, inheriting, and animating local Culture in attractions, access, amenities, ancillary, safeness, and comfort. The role of youth in developing local Culture to develop tourism in Sabang City could be seen with youth's enthusiasm in disseminating, assessing, and enriching local cultural diversity in attractions, access, amenities, ancillary, safeness, and comfort. The role of youth in utilizing to develop tourism in the city of Sabang could be seen with the enthusiasm of youth in increasing cultural resilience, improving youth welfare, and innovating local cultural attractions, access, amenities, ancillary, safeness, and comfort. Thus, the role of youth in preserving local Culture is needed in developing tourism in the city of Sabang.